The effect of green coconut water consumption on reducing the intensity of dysmenorrhea in adolescent girls - Ana Mariza; Endang Tri Wulandari; Fijri Rachmawati; Nurul Isnaini (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Dysmenorrhea in adolescent girls occurs due to hormonal imbalances, particularly a decrease in progesterone levels in the blood, resulting in pain during menstruation. The prevalence of dysmenorrhea in Indonesia is 64.25%, and the results of a pre-survey of 15 adolescents girls who had menstruated at SMPN 2 Seputih Banyak on February 17, 2025 showed that 7 (46.7%) of them experienced dysmenorrhea. If left untreated, dysmenorrhea can lead to pathological conditions, potentially increasing mortality rates and contributing to infertility. One of the alternative efforts to alleviate dysmenorrhea is through the consumption of green coconut water. Purpose: to determine the effect of green coconut water consumption on the reduction of dysmenorrhea intensity among adolescent girls. Method: This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The population consisted of all eighth-grade female students at SMPN 2 Seputih Banyak, totaling 57 individuals, with a sample of 30 participants. The sample was divided equally into an experimental group (15 participants) and a control group (15 participants), selected using purposive sampling. Data analysis was conducted using the Mann-Whitney test. Results: The results showed a decrease in the average dysmenorrhea pain score in the intervention group from 5.04 before the administration of green coconut water to 1.93 afterward. Meanwhile, in the control group, the average pain score decreased from 5.13 during the pretest to 2.93 in the posttest, despite no intervention being given. Statistical analysis indicated a significant effect of green coconut water consumption on reducing the intensity of dysmenorrhea in adolescent girls, with a p-value of 0.000. Conclusion: Indicated a significant effect of green coconut water consumption on reducing the intensity of dysmenorrhea in adolescent girls. Suggestion: The adolescent girls expected consider green coconut water as a natural alternative for relieving dysmenorrhea.